FRI0409 The Association Between Antiphospholipid Antibody Profile and Adverse Pregnancy Outcome in 217 Prospectively Followed, Treated Pregnancies in a Single Center Over 30 Years of Experience. (9th June 2015) - Lazzaroni, M.G.; Lupoli, F.; Aggogeri, E.; Bettiga, E.; Andreoli, L.; Fredi, M.; Reggia, R.; Lojacono, A.; Zatti, S.; Taglietti, M.; Gorla, R.; Filippini, M.; et al.
Abstract : Background: Antiphospholipid antibodies (aPL) are risk factors for adverse pregnancy outcome (APO). Still debated is the prognostic role of the aPL profile, defined as the combination of the 3 criteria tests for aPL (LA: Lupus Anticoagulant; aCL: anti-cardiolipin; aB2GPI: anti-beta2glycoprotein I) and the antibody titer (low vs. medium-high) of aCL and aB2GPI. Objectives: To determine the association between the aPL profile and the occurrence of APO in prospectively followed, treated pregnancies. Methods: 217 pregnancies in 154 women were prospectively followed by a multidisciplinary team of rheumatologists and obstetricians in a single center between 1985 and 2014. Patients were classified as Primary Antiphospholipid Syndrome (PAPS) according to the revised criteria. Patients not fulfilling the criteria, were defined as either non-criteria PAPS or aPL carriers, according to their clinical history and/or aPL status. Patients with concomitant systemic autoimmune diseases were excluded. Data were retrospectively collected and analyzed by aPL profile categories. APO was defined as at least one of the following: miscarriage (before 10th week), fetal death (beyond 10th week), severe preterm delivery (before 34th week) with or without preeclampsia (PE), HELLP syndrome or perinatal death. Statistical analysis was performed with Chi-square with Yates' correction (p-value significant <0.05). Results: The serological profile (triple, double, single aPL positivity) and diagnostic classification of the 217 pregnancies is shown in Table 1 . APO occurred in 33 (15%) pregnancies: 14 (42%) in triple positive, 5 (15%) in double positive, and 14 (42%) in single positive patients. Fifteen APO (45%) occurred in LA negative pregnancies. Triple aPL positivity was significantly associated with APO in comparison with double + single positivity (χ2=5.61, p=0.006). In order to assess the role of antibody titers, the analysis was restricted to pregnancies positive for each single aPL test (IgG/IgM aCL, IgG/IgM aB2GPI). No difference in the frequency of APO was observed between pregnancies with low vs. medium-high titer for IgG aCL, IgM aCL, and IgM aB2GPI. Medium-high titers of IgG aB2GPI were associated with APO in comparison with low titers, respectively 17 pregnancies (27%) vs 4 pregnancies (8%) (χ2=5.20, p=0.02). Among these 17 pregnancies with medium/high titers, 13 (76%) were triple aPL positive. Conclusions: Patients with triple aPL positivity seem to be at higher risk for APO despite conventional treatment. aCL and aBGPI titers do not seem to be associated with APO, therefore patients in our cohort with low titers cannot be considered at "low risk" for obstetric events, although being treated. Disclosure of Interest: None declared